Sin and human responsibility in the theology of Emil Brunner - Grant, Malcolm Colin (The University of Edinburgh, 1967)
Brunner's theology is one of reaction and reformulation; reaction against the "objectivism" of Orthodoxy and Roman Catholicism, and against the "subjectivism" of liberal theology, and a reformulation of the basic tenets of the Christian faith in accordance with the sola gratia perspective of the Reformers. The reformulation contrasts the competing tendencies in philosophy, psychology and ethics, and relates these to the basic contradiction of human life, which the Christian faith calls 'sin', with the aid of Kantian criticism, and particularly Kantian moral theory, the Kierkegaardian dialectic of time and eternity, and the I-Thou framework developed by Ebner and Buber. Within this comprehensive formulation, our concern is the question of sin and human responsibility.

Theologically, the issue is the seriousness of sin, and has been answered traditionally by contrasting man's creation in the image of God with the loss of that image through sin. Brunner's contention that Scripture presents two concepts of the image is most plausible, but his designation of these as a formal and a material concept of the image seems to set the distinction within man himself, whereas the Scriptural distinction seems to be between an Old Testament image which is predicated of man and a New Testament image which is Christ. We must also question his contention that Irenaeus distinguished between imago and similitudo in a manner similar to the medieval natural-supernatural distinction, but his summation of the Reformers' predicament, that their equation of the image with the justitia originalis and corresponding doctrine of total depravity renders their concept of a 'relic' of the image illegitimate, is essentially plausible. Brunner's solution to this predicament is not greatly clarified in the controversy with Barth, although Barth's subsequent charge, that Brunner teaches a neutral freedom, is instructive. Brunner's insistence on a concept of an analogia entis involving an analogy of proportionality, likeness in basic unlikeness, is understandable, but his relational interpretation of this suggests that his distinction between a formal and a material sense of the image is facilitated by an ambiguity in the term 'responsibility'.

The term 'responsibility' seems to have at least three basic meanings in Brunner's theology - responsiveness, accountability, and ability to respond. Behind this is the more basic question of the distinction between moral and religious responsibility. His enthusiasm for Kant's development of the concept suggests that he overlooks the basically rational nature of the Kantian Imperative, and his content- -ion that Kant was torn between autonomy and theonomy suggests that he minimises the rational perspective from which Kant viewed Christianity. Kierkegaard's teleological suspension of the ethical, with its inseparability of command and commanded, reveals the difficulty in the formal Kantian Imperative which Brunner applauds. Further, Brunner's contention that Kant's concept of 'radical evil' is rationally discerned, and his appreciation for Schelling's treatment of evil, cast doubt on the seriousness of his affirmation of the irrationality of sin, and also illuminate the ambiguity in the moral and religious uses of the term 'responsibility' in his writings. There seem to be two strands in Brunner's presentation - a basic allegiance to the Reformers, and a certain sympathy with moral idealism.

The conflict is climaxed in Brunner's treatment of the Fall and Original Sin. His rejection of a literal interpretation of Genesis III is understandable, but his contention that there is no real conflict here with modem science indicates an oversimplification of the problem. His rejection of a causal explanation of sin is understandable, but his rejection of every temporal explanation suggests a confusion between causal and temporal. His late admission that he taught a Platonic doctrine of the Fall suggests that he never really came to grips with the basic problems of the doctrine. His concern has been with the fallenness of man, in which he attempts to correct the one-sidedness of the Augustinian doctrine with an emphasis on responsibility. Here the conflict between the two strands in Brunner's theology is pronounced. His reversal of Kierkegaard's formula for the relation between individuals and humanity, whereby the special term 'Individual' is subordinated to an individualistic concept of 'each of us', conflicts with his concern for solidarity and his appreciation for the I-Thou framework, but agrees with his emphasis on responsibility and his refusal to consider a temporal origin of sin. Ultimately it is the universality of sin, and not solidarity in sin, which prevails in Brunner's theology. As this fails to provide an adequate statement of the totality of sin in terms of the race, so his emphasis on sin as 'act' fails to give adequate account of the totality of sin in terms of the individual. The concern to emphasise responsibility for sin suggests that this is a total responsibility which is predicated of men in general, and thus indicates a violation of the Reformation perspective.

In his basic allegiance to the Reformation perspective, Brunner's development of the sola gratia principle involves an opposition to synergism in Orthodoxy, Roman Catholicism and liberal theology, and to passivism in the Reformers themselves. His defence of the personal over against the rational, in terms of the I-Thou framework, raises questions as to the significance of the 'It'dimension of life and the nature of the relation between I and Thou. The two questions are answered in Brunner's presentation of the respective roles of the imperative and the indicative in the relation. The former reveals a basic divergence between Brunner and Luther on 'Law' in that Brunner divests Luther's Law of all content and reintroduces it as the formal Imperative, thus indicating that Law is an 'It' which has no integral place in the I-Thou framework. The indicative of the once-for-all act of God in Christ is equally embarrassing to the I-Thou, although it represents a constant emphasis in Brunner's theology. Luther's concern for the man who stands between the demand of the Law and the comfort of the Gospel becomes, in Brunner, the concern to relate this dialectic to the self-understanding of natural man. He accomplishes this with the relatively modern word 'responsibility' which can refer both to man as an independent moral agent and to man's ultimate obligation to God. In so far as man is addressed as a moral agent, and called to account prior to the proclamation of grace, the Reformation perspective is violated. It is strange that Brunner has not applied his recognition of the profound gulf separating modern man from former ages to this relatively modern concept of 'responsibility'.